KORELASI ANTARA PENDIDIKAN ROHANI TERHADAP AKHLAK SISWA KELAS XI IPS DI MA HASAN MUCHYI KAPUREJO KEDIRI - Khoirur Roziqin, Muhamad; Muawanah, Risalatul (ILJ: Islamic Learning Journal, 2023)
The rise of juvenile delinquency, promiscuity and increased crime everywhere is a reality symptomatic of moral decline at the adolescent level that occurs in today's society. This raises the assumption that education has not been able to shape students into perfect personalities. This assumption makes education an institution that is considered a failure in shaping the noble morals of students. Even though the purpose of education is to form a person with character, dignity, faith, piety, and morality. The purpose of this study was to determine the implementation of spiritual education, student morals and the relationship between the two in grade XI social studies students at MA Hasan Muchyi Kapurejo Kediri. This study used quantitative methods. The results of this study revealed that spiritual education is a process carried out to guide the soul as an effort to improve the relationship with Allah SWT. While morals are the power of strength or nature embedded in a person's soul so that they become personality characteristics and encourage action to do an action. This study also shows the results that there is a correlation between spiritual education and student morals. This is based on the results of data analysis that has been carried out, namely: Spiritual education is in the medium category with a frequency of 30 students and a percentage of 56%. Student morals are in the medium category with a frequency of 26 students and a percentage of 48%. As well as the correlation between spiritual education and student morals, the results of = 0.586 were obtained which were in the position of 0.40 – 0.599 with a moderate level of relationship.